Friendship in UiTM Machang / Siti Aswani Mohd Ghazali and Junaidi Awang - Mohd Ghazali, Siti Aswani; Awang, Junaidi (Faculty of Art and Design, 2021)
Friendship is the hardest thing in the world to explain. It’s not something you learn in school. But if you haven’t learned the meaning of friendship, you really haven’t learned anything. It may be difficult to put into words how thankful you are for your friend. Close friends are everywhere, close friends at work are very important as they are the backbone and determinant of my mood all day in the place of earning a living. Subconsciously we have been together in UiTM Machang for more than 15 years. It is a period full of memories, challenges, trials, yer our career’s journey is still long and we will continue to fight. Don’t make friends who are comfortable to be with. Make friends who will force you to lever yourself up.. Life is partly what we make it, and partly what it is made by the friends we choose…let’s think about it.